The passion of Dolssa - Berry, Julie, 1974- (Viking, 2016)
In mid-thirteenth century Provence, Dolssa de Stigata is a fervently religious girl who feels the call to preach, condemned by the Inquisition as an "unnatural woman," and hunted by the Dominican Friar Lucien who fears a resurgence of the Albigensian heresy; Botille is a matchmaker trying to protect her sisters from being branded as gypsies or witches--but when she finds the hunted Dolssa dying on a hillside, she feels compelled to protect her, a decision that may cost her everything.